Pengaruh Persepsi Kegunaan dan Persepsi Kemudahan Terhadap Penggunaan ShopeePay - Baiq Inten Diah Witari; Karim, Nina Karina (Jurnal Riset Mahasiswa Akuntansi, 2024)
This study aims to analyze the effect of perceived usefulness and perceived ease of use on ShopeePay usage. This research uses a quantitative associative approach with a purposive sampling technique, where respondents are the people of Mataram city aged 17-35 years. Data were collected through questionnaires from 105 respondents and analyzed using multiple linear regression. The results of the study show that perceived usefulness has a positive and significant effect on ShopeePay usage, while perceived ease of use does not have a significant effect on ShopeePay usage.